Implementation of Work in Progress Adjustment Form at PT PLN Nusantara Power - Pratama Nugraha, Rizal; Anjar Nugroho, Rizki; Sulistijono, Primaditya (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Work In Progress Form is a tool that is used to assess the occupational safety and health program of contractors. However, the Work in Progress Form currently used is made using only best practices. which can increase the risk of work accidents because it does not follow SMK3. Therefore, adjustments need to be made to the current Work in Progress Form. After adjustments were made, the Work In Progress Form which was initially only following 18 of 64 criteria of SMK3 based on PP No. 50 of 2012 at the Initial Level, then after being adjusted, it now follows 38 of 64 SMK3 at initial Level. The implementation of SMK3 at Initial Level was chosen because it's in the project phase. Back then, contractors always got 100% score. When an assessment was carried out using the adjusted Work In Progress Form, for the contractor PLN NPC received score of 90.53% in April 2024 then increased to 95.52% in May 2024. Meanwhile, for the contractor PLN NPS in April 2024, PLN NPS received a score of 88.06% then increased to 93.28% in May 2024. It’s because the form is more in line with SMK3 PP No. 50 of 2012 Initial Level.